Sarcopenia and Age-Related Endocrine Function - Kunihiro Sakuma; Akihiko Yamaguchi (International Journal of Endocrinology)
Sarcopenia, the age-related loss of skeletal muscle, is characterized by a deterioration of muscle quantity and quality leading to a gradual slowing of movement, a decline in strength and power, and an increased risk of fall-related injuries. Since sarcopenia is largely attributed to various molecular mediators affecting fiber size, mitochondrial homeostasis, and apoptosis, numerous targets exist for drug discovery. In this paper, we summarize the current understanding of the endocrine contribution to sarcopenia and provide an update on hormonal intervention to try to improve endocrine defects. Myostatin inhibition seems to be the most interesting strategy for attenuating sarcopenia other than resistance training with amino acid supplementation. Testosterone supplementation in large amounts and at low frequency improves muscle defects with aging but has several side effects. Although IGF-I is a potent regulator of muscle mass, its therapeutic use has not had a positive effect probably due to local IGF-I resistance. Treatment with ghrelin may ameliorate the muscle atrophy elicited by age-dependent decreases in growth hormone. Ghrelin is an interesting candidate because it is orally active, avoiding the need for injections. A more comprehensive knowledge of vitamin-D-related mechanisms is needed to utilize this nutrient to prevent sarcopenia.